Literatur Review Metode Evaluasi Kualitas Usability Website - Kulakat, Aldy A; Utami, Ema; Wibowo, Ferry Wahyu (Jurnal Ilmiah SINUS, 2021)
Website is a collection of online documents containing Web pages that are moored in a domain as a unique name. It can be accessed via the Internet so that existing information can be displayed and accessed by Web visitors. Web visitors tends to need websites with user interface which is easy to use, to interact (usability), or communicate in sharing information. There are basically some benchmarks that can be used to measure website usability, including (1) Learnability, easiness to learn; (2) Efficiency, user speed level; (3) memorability, easiness to remember; (4) Error and safety, low fault rate; and (6) Satisfaction, satisfied user. Moreover, there are several methods of evaluation of the website in this research, such as: (1) Thinking Aloud Method, (2) User Perfomance test, (3) Remote Usability Test, (4) Cooperative Evaluation, (5) Expert Review, (6) Heuristic Evaluation, (7) Cognitive Walkthrough, (8) Plurastic Walkthrough, (9) Field Observation, and (10) Interview and Focus group.Â Â In addition, the selection of a questionnaire or sampling deployment method and designing interface method may also affect the outcome of the evaluation of the website.